Why ARMAX-GARCH linear models successfully describe complex nonlinear phenomena: A possible explanation - Hung T. Nguyen (2018)
© Springer International Publishing Switzerland 2015. Economic and financial processes are complex and highly nonlinear. However, somewhat surprisingly, linear models like ARMAXGARCH often describe these processes reasonably well. In this paper, we provide a possible explanation for the empirical success of these models.